2017
DOI: 10.3382/ps/pew189
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to fibroblast growth factor 23-peptide reduces excreta phosphorus of laying hens

Abstract: Novel strategies to minimize the excretion of phosphorus in swine and poultry are critical in minimizing environmental degradation. We have developed a synthetic peptide vaccine to produce autoantibodies to fibroblast growth factor 23 (FGF-23), a bone-derived hormone that blocks kidney phosphate resorption and indirectly reduces intestinal phosphate absorption. Single Comb White Leghorn laying hens, fed a standard diet (inorganic phosphorus, Pi = 0.4%), were immunized over the course of 4 weeks with either a F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Statistical significance was considered at P < 0.05 and trends at P < 0.1. According to our previous data (Ren et al, 2017c), seven laying hens per treatment would be sufficient to reflect the influences of dietary phosphorus levels on serum phosphorus concentrations (two means, 1.32 compared to 2.11 mmol/L, with two-sided significance of P < 0.05, with a pooled standard error of 0.50). As expected, in experiment 2, a statistical power of > 0.80 and a two-sided significance of P < 0.001 were obtained on serum phosphate concentrations by sampling seven laying hens from each experimental diet.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance was considered at P < 0.05 and trends at P < 0.1. According to our previous data (Ren et al, 2017c), seven laying hens per treatment would be sufficient to reflect the influences of dietary phosphorus levels on serum phosphorus concentrations (two means, 1.32 compared to 2.11 mmol/L, with two-sided significance of P < 0.05, with a pooled standard error of 0.50). As expected, in experiment 2, a statistical power of > 0.80 and a two-sided significance of P < 0.001 were obtained on serum phosphate concentrations by sampling seven laying hens from each experimental diet.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) reported that the perfusions of 1,25-dihydroxy-cholecalciferol [ 1,25(OH) 2 D 3 ] or parathyroid hormone ( PTH ) fragment (1-34) increased intestinal expressions (both mRNA and protein levels) of type IIb sodium-phosphate cotransporter ( NaPi-IIb ) and thereby enhanced phosphorus absorption in broilers. A Wisconsin group found that antibodies to fibroblast growth factor 23 were effective in increasing renal phosphate resorption and decreasing phosphate requirements and excretions in laying hens and its progeny chicks ( Ren et al., 2017a , Ren et al., 2017b , Ren et al., 2017c ). In addition, phytase, the most widely used dietary exogenous enzyme in animal production ( Adeola, 2011 ), breaks down phytate-phosphate from plant feed ingredients and dramatically reduces the animals' requirement for inorganic phosphorus ( Fernández et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It could also induce the decrease of 1.25(OH) 2 D 3 plasma levels by the up regulation of the 24 hydroxylase gene in the kidney 18 . As active immunization of hens against FGF23 increases P retention 19 , these observations highlight this factor as an important regulator of the Ca/P balance in laying hens.…”
mentioning
confidence: 71%
“…Further research is needed to test strategies to improve the management of old hens. A first strategy could selectively target circulating FGF23, for example by immunization as previously tested in younger hens 19 . A second strategy could rely upon a better adaptation of dietary P supply to the needs of old hens, saving this nonrenewable resource and limiting the stimulation of FGF23 production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation